Pronomes de tratamento no português brasileiro no limiar do século XX: uma análise sociopragmática - Valentim, Marinalda Freitas (2017)
This research intends to describe the chart of treatment pronouns in the Letters to Severino Vieira – Governor of Bahia (1901-1902), as well as, from a sociopragmatic perspective, to carry out a quantitative and qualitative analysis of the data with the intention of presenting a general picture of the use of the treatment forms. In this context, it is sought to observe the distribution of treatment strategies according to the communicative situation established between sender and recipient, according to the theory of Power and Solidarity (BROWN; GILMAN, 1960) and Theory of Politeness (BROWN; LEVINSON, 1989). Data analysis also takes into account the theoretical assumptions of Laovian sociolinguistics (WEINREICH; LABOV; HERZOG, 1968) in order to identify the factors that condition the alternate use of treatment pronouns in the sample under analysis. In order to do so, both the value that the form of treatment carries, in view of the characteristics of the speaker (age, sex, education, social group, etc.) in relation to the recipient is taken into account, observing linguistic and extralinguistic conditioning, such as Justification for what form of treatment has been employed and the effect that such choice may have on the recipient in the interaction. The corpus used is the Letters collection for Severino Vieira, whose content is composed of 102 texts, extracted from Carneiro (2005), sent to Severino Vieira by 60 senders (57 men and 03 women), most of them literate and mainly residents in cities. The letters that compose the collection are written mostly by Brazilians. In relation to the results, these show a preference of the letter writers for a more ceremonial treatment. Thus, a nature of the relationship established between the senders and Governor Severino Vieira was classified as ascending asymmetry, which explains a high occurrence of the nominal form of Your Excellency. This result confirms the idea that there is a close relationship between forms of treatment and social roles.